On the optical anisotropy in 2D metal-halide perovskites. Issue 3 (23rd December 2021) - Steger, Mark; Janke, Svenja M.; Sercel, Peter C.; Larson, Bryon W.; Lu, Haipeng; Qin, Xixi; Yu, Victor Wen-zhe; Blum, Volker; Blackburn, Jeffrey L.
Abstract : We develop a better understanding of the many contributing factors that give rise to extreme optical anisotropy in 2D perovskites, and we then show that spin-coated films can exhibit excellent order comparable with exfoliated crystals. Abstract : Two-dimensional metal-halide perovskites (MHPs) are versatile solution-processed organic/inorganic quantum wells where the structural anisotropy creates profound anisotropy in their electronic and excitonic properties and associated optical constants. We here employ a wholistic framework, based on semiempirical modeling (k·p/effective mass theory calculations) informed by hybrid density functional theory (DFT) and multimodal spectroscopic ellipsometry on (C6 H5 (CH2 )2 NH3 )2 PbI4 films and crystals, that allows us to link the observed optical properties and anisotropy precisely to the underlying physical parameters that shape the electronic structure of a layered MHP. We find substantial frequency-dependent anisotropy in the optical constants and close correspondence between experiment and theory, demonstrating a high degree of in-plane alignment of the two-dimensional planes in both spin-coated thin films and cleaved single crystals made in this study. Hybrid DFT results elucidate the degree to which organic and inorganic frontier orbitals contribute to optical transitions polarized along a particular axis. The combined experimental and theoretical approach enables us to estimate the fundamental electronic bandgap of 2.65–2.68 eV in this prototypical 2D perovskite and to determine the spin–orbit coupling ( Δ SO = 1.20 eV) and effective crystal field ( δ = −1.36 eV) which break the degeneracy of the frontier conduction band states and determine the exciton fine structure. The methods and results described here afford a better understanding of the connection between structure and induced optical anisotropy in quantum-confined MHPs, an important structure–property relationship for optoelectronic applications and devices.